CREATION of the UNIVERSE by AL-QUR'AN Analysis of QS. Al-Anbiya: 30 and Its Relevance to the Theory of Science - Munziri Ali (Madania: Jurnal Ilmu-Ilmu Keislaman, 2012)
The term of ‘alam has similiarity with ilm in Arabic. This indicates that there is a close connection between a concept of knowledge with the obligation to explore the nature. One of surah in Qur’an which discusses about the nature is al-anbiya’ : 30. In this verse, God says that sky and earth are basically unified coherently so that they are like one mass. This is in line with the most recent finding of the nature theory. Based on this theory, thousand years ago, the nature was accumulated strongly in the form of ball with which its trellis   is not more than 3.000.000 mile.